Pengajaran Baca Tulis Al-Qur'an bagi Tunanetra: Studi pada Tiga Lembaga - Syatri, Jonni (SUHUF, 2016)
As the scripture, every Muslim has the right to access the Qur’an, especially to read, even for people with disabilities such as the visual impairment. Due to the limitations of their sight, the Qur’an with the Braille script are provided and available for the blind people. This paper discusses the teaching of reading and writing of the Qur'an with Braille script for the visual impaired at the three institutions located in Bandung, in Payakumbuh, and in Tebing Tinggi, West Sumatra. These three agencies make the teaching of the Qur'an as one of the programs provided for the students. Of the three institutions, that already has a pretty good system of teaching is Wyata Guna Bandung with the systematic curriculum and syllabus, as well as textbooks. As for the two other institutions, the methods of are still based on the experience of the teachers and the textbooks are even not available, and are not using the books from other institutions. The same teaching system and standard to be used by all institutions teaching the Qur’an with Braille script have not been found yet. However, these three institutions have in common by adopting the same Bagdadi method for their teaching delivery.